1989
DOI: 10.1002/jso.2930410305
|View full text |Cite
|
Sign up to set email alerts
|

Partial nephrectomy in mice with milliwatt carbon dioxide laser and its influence on experimental metastasis

Abstract: We have developed a surgical model to perform partial nephrectomy in mice using the milliwatt CO2 laser and have used this model for studying the influence of the sequel of surgery on experimental tumor metastasis. Strain A mice were subjected to partial nephrectomy using the milliwatt CO2 laser. The surgical procedure was time efficient, the blood loss was minimal, and the postoperative mortality was 6%. Immediately after surgery, the wound consisted of a superficial layer of charring and a deeper layer of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In addition to this difficulty, even those xenografts that are derived from metastatic tumors fail to metastasize in the host animals. with l0 s cells develop tumors in these organs [10][11][12]. Despite this aggressiveness, TA3Ha cells rarely implant and grow in the kidney, liver, spleen, cecum, or the bones [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this difficulty, even those xenografts that are derived from metastatic tumors fail to metastasize in the host animals. with l0 s cells develop tumors in these organs [10][11][12]. Despite this aggressiveness, TA3Ha cells rarely implant and grow in the kidney, liver, spleen, cecum, or the bones [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…injected syngeneic TA3Ha tumor cells selectively implant at sites of hepatic trauma induced by electrocautery [6,7]. Tumor implantation has also been noted in mice following surgery of the kidney, skin, caecum, spleen, or the pelvic bone [5][6][7]; in the absence of trauma, these sites are rarely affected by metastases [18,19]. In all the sites so far examined, the highest rate of tumor implantation in the wounds was seen when tumor cells were injected immediately after surgery [5][6][7]; as the interval between surgery and tumor cell inoculation increased the frequency of tumor implantation decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that injury resulting from surgical [1][2][3][4][5][6][7][8] or mechanical trauma [9,10], exposure to radiation and chemicals [11][12][13][14][15], and treatment with anticancer drugs [16,17] favors tumor implantation in healing wounds. Our focus has been on implantation of i.v.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations